2021
DOI: 10.1038/s41427-021-00303-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve photodynamic therapy efficacy by relieving the tumor hypoxia environment

Abstract: Photodynamic therapy (PDT) is an emerging technology for tumor treatment in which photosensitizer (PS)-mediated light irradiation reduces oxygen, producing high levels of reactive oxygen species (ROS) that can cause vascular injury and effectively kill tumor cells. However, the naturally hypoxic tumor microenvironment is the main obstacle that hinders the photodynamic response in vivo and prevents its extensive application to tumor treatment. Moreover, PDT-mediated oxygen consumption further increases tumor hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 99 publications
1
90
0
Order By: Relevance
“…The elevated GSH level found in tumor cells confers them therapeutic resistance by preserving the levels of cysteine and detoxification of xenobiotics [75]. Previous studies suggest that overexpression of GSH might be also correlated with resistance to PDT [76,77]. In the current study, we found that the treatment with γ-Fe 2 O 3 NPs_TPPS under 1 min irradiation induced a slight elevation of GSH synthesis compared to control as a response to high ROS production.…”
Section: Discussionsupporting
confidence: 58%
“…The elevated GSH level found in tumor cells confers them therapeutic resistance by preserving the levels of cysteine and detoxification of xenobiotics [75]. Previous studies suggest that overexpression of GSH might be also correlated with resistance to PDT [76,77]. In the current study, we found that the treatment with γ-Fe 2 O 3 NPs_TPPS under 1 min irradiation induced a slight elevation of GSH synthesis compared to control as a response to high ROS production.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, the effects of PDT are mainly limited to the area of photosensitization (Moan and Berg, 1991). Given the fact that PDT is highly dependent on the presence of oxygen in the tissues, tumor hypoxia can significantly hamper the effectiveness of PDT (Bhandari et al, 2019;Shen et al, 2021). Indeed, depletion of oxygen due to PDT itself might also decrease PDT efficiency.…”
Section: Limitations Of Photodynamic Therapymentioning
confidence: 99%
“…[151] As another example, uncontrolled cell proliferation in a tumor forms hypoxic areas that create complex and inimical effects regarding tumor progression and therapy resistance. [152] We should also consider that in vivo cells are often exposed to 2-5% oxygen levels, while in vitro culture systems are usually maintained at the atmospheric oxygen levels (20% O 2 and 5% CO 2 ). O 2 levels affect and trigger cell metabolism and functionality; [153] thus, it is essential to simulate and track O 2 levels in vitro.…”
Section: Optical Biosensors For Measuring Extracellular Parametersmentioning
confidence: 99%